Wegener's granulomatosis simulated by a T cell lymphoma of the lung. Issue 6 (June 1991) - Small, J H; Round, Alison; Simpson, R H W; Ferguson, A D
Abstract : A case of primary T cell lymphoma of the lung associated with antineutrophil cytoplasmic antibody simulated Wegener's granulomatosis, the patient having features compatible with but not diagnostic of Wegener's granulomatosis.